Dual wave of neutrophil recruitment determines the outcome of C. albicans infection - Zhu, Weiwei; Zhang, Huifang; Dong, Qiming; Song, Hongyong; Zhao, Lin (Frontiers in Cellular and Infection Microbiology, 2023)
Candida albicans is a ubiquitous fungus that can cause superficial and systemic infections in humans. Neutrophils play a crucial role in controlling C. albicans infections. When C. albicans enters the bloodstream, it tends to get trapped in capillary vessels. However, the behavior of neutrophils in combating capillary-residing fungi has not been fully characterized. In this study, we used transgenic mice and whole mount imaging to investigate the growth of C. albicans and its interaction with innate immune cells in different organs. We observed that C. albicans rapidly grows hyphae within hours of infection. Following intravenous infection, we observed two waves of neutrophil recruitment, both of which significantly contributed to the elimination of the fungi. The first wave of neutrophils was induced by complement activation and could be prevented by C5aR blockade. Interestingly, we discovered that the fungicidal effect in the lungs was independent of adhesion molecules such as Mac-1, LFA-1, and ICAM-1. However, these molecules played a more significant role in the optimal killing of C. albicans in the kidney. Importantly, the initial difference in killing efficiency resulted in significantly reduced survival in knockout mice lacking these adhesion molecules. We identified a second wave of neutrophil recruitment associated with hyphal growth and tissue damage, which was independent of the aforementioned adhesion molecules. Overall, this study elucidates the dual wave of neutrophil recruitment during C. albicans infection and highlights the importance of early fungal clearance for favorable disease outcomes.